2022
DOI: 10.2528/pierm21100701
|View full text |Cite
|
Sign up to set email alerts
|

A Triple Band Highly Sensitive Refractive Index Sensor Using Terahertz Metamaterial Perfect Absorber

Abstract: This research introduces a novel design of a metamaterial absorber having the range in terahertz, capable of sensing changes in the refractive index of the encircling medium. The layout includes adjoining rectangular patches in the form of a plus symbol along with four circular patch resonators (CPRs) on the pinnacle of a Gallium Arsenide (GaAs) substrate. The proposed design comes up with three consecutive absorption peaks, with an absorptivity of 99.0%, 99.75%, and 98.0% at three different resonant frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…An important application of terahertz metamaterial absorbers is in sensing. The absorption spectrum of the absorbers varies with the changes in the physical parameters such as, refractive index of the analyte [22], analyte depth [23], and temperature of the surrounding medium [24]. Thus, refractive index sensors, temperature sensors, hybrid sensors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…An important application of terahertz metamaterial absorbers is in sensing. The absorption spectrum of the absorbers varies with the changes in the physical parameters such as, refractive index of the analyte [22], analyte depth [23], and temperature of the surrounding medium [24]. Thus, refractive index sensors, temperature sensors, hybrid sensors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve wideband operation in the THz operating region, several multilayer metamaterial structures have been demonstrated that show high absorption peaks due to different structures [20][21][22][23][24][25][26][27][28][29][30]. These multilayer metamaterial-based absorbers have complex designs and a difficult fabrication process, leading them to show complications in integrating with commercial technologies and therefore ultimately increasing the cost.…”
Section: Introductionmentioning
confidence: 99%